Incident HIV among pregnant and breast-feeding women in sub-Saharan Africa: a systematic review and meta-analysis. (1st April 2020) - Graybill, Lauren A.; Kasaro, Margaret; Freeborn, Kellie; Walker, Jennifer S.; Poole, Charles; Powers, Kimberly A.; Mollan, Katie R.; Rosenberg, Nora E.; Vermund, Sten H.; Mutale, Wilbroad; Chi, Benjamin H.
Abstract : Objectives: A previous meta-analysis reported high HIV incidence among pregnant and breast-feeding women in sub-Saharan Africa (SSA), but limited evidence of elevated risk of HIV acquisition during pregnancy or breast-feeding when compared with nonpregnant periods. The rapidly evolving HIV prevention and treatment landscape since publication of this review may have important implications for maternal HIV incidence. Design: Systematic review and meta-analysis. Methods: We searched four databases and abstracts from relevant conferences through 1 December 2018, for literature on maternal HIV incidence in SSA. We used random-effects meta-analysis to summarize incidence rates and ratios, and to estimate 95% prediction intervals. We evaluated potential sources of heterogeneity with random-effects meta-regression. Results: Thirty-seven publications contributed 100 758 person-years of follow-up. The estimated average HIV incidence rate among pregnant and breast-feeding women was 3.6 per 100 person-years (95% prediction interval: 1.2–11.1), while the estimated average associations between pregnancy and risk of HIV acquisition, and breast-feeding and risk of HIV acquisition, were close to the null. Wide 95% prediction intervals around summary estimates highlighted the variability of HIV incidence across populations of pregnant and breast-feeding women in SSA. Average HIV incidence appeared associated with age, partner HIV status, and calendar time. Average incidence was highest among studies conducted pre-2010 (4.1/100 person-years, 95% prediction interval: 1.1–12.2) and lowest among studies conducted post-2014 (2.1/100 person-years, 95% prediction interval: 0.7–6.5). Conclusion: Substantial HIV incidence among pregnant and breast-feeding women in SSA, even in the current era of combination HIV prevention and treatment, underscores the need for prevention tailored to high-risk pregnant and breast-feeding women. Abstract : Supplemental Digital Content is available in the text